2021
DOI: 10.3389/feduc.2021.618323
|View full text |Cite
|
Sign up to set email alerts
|

Responses to COVID-19 From Non-State School Leaders in Latin America, Sub-Saharan Africa and, India: A Call for Educational Equity

Abstract: In early 2020, the rapid spread of the COVID-19 pandemic was an unprecedented shock to the global education system, resulting in most educational institutions closing their doors and turning to various forms of remote learning to ensure continuous education for their communities. Since the world has not experienced this scale of school closure before, the goal of this study was to explore what, if anything, non-state schools (NNSs) were doing to support remote learning that may help them to prepare for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Prior research has indicated, for example, that COVID-19 has created an unprecedented crisis with numerous and ongoing challenges to educational systems around the world (Rincones et al, 2021). These challenges required both adaptive and contingent leadership, including targeted responses to the social, emotional, mental health and academic needs of students and school staff (e.g., Moss et al, 2020;Cordeiro et al, 2021;Greany et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has indicated, for example, that COVID-19 has created an unprecedented crisis with numerous and ongoing challenges to educational systems around the world (Rincones et al, 2021). These challenges required both adaptive and contingent leadership, including targeted responses to the social, emotional, mental health and academic needs of students and school staff (e.g., Moss et al, 2020;Cordeiro et al, 2021;Greany et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding is associated with education equity (Cordeiro et al, 2021): the responses to COVID-19 From non-state school leaders in Latin America, sub-Saharan Africa, and India point to the support provided during school closures (35% of the participants indicated that they offered some support through technology and 53% through paper methods). Technologies utilised included messaging apps, video or audio conferencing, and/or LMS.…”
Section: School Management Practices and Digital Technologies During ...mentioning
confidence: 99%
“…The students also experienced stress in maintaining their education, particularly those in higher education, who, normally more independent, could afford such transition by their means, still had to address diverse family, economic, and curriculum factors and environments [26]. In any case, the situation for public and private schools generally lived differently [27].…”
Section: Changes Losses and Gains In Learning Due To The Covid-19 Con...mentioning
confidence: 99%